Typology of Slavic Menaia Manuscripts Dated from 11th to 17th Centuries and Information Search Methods - Нечунаева, Наталья Алексеевна Алексеевна; Нечунаев, Алексей Владимирович Владимирович (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The Menaion has a profound value in the history of Slavic languages. Previous literature applies linguistic-textological methodology to reveal a textological typology of Menaia. On the contrary, this article uses data-driven methods to classify these Old Slavic manuscripts. A vector space model is established to analyse ten Menaia manuscripts represented by a common text fragment. Analysis of various distance measures reveals similarity and differences among the analyzed manuscripts.
Keywords: Menaion, text composition, text structure, information search